K-α x-ray measurements and their applicability for fast electron generation and transport studies in ultrashort intense laser foil interaction. (9th August 2021) - Mandal, T; Arora, V; Moorti, A; Chakera, J A
Abstract: K- α x-ray measurements using a high-resolution highly annealed pyrolytic graphite crystal spectrograph have been performed for ultrashort intense laser foil interaction. Experiments were performed using Ti:sapphire laser of 25 fs duration, intensity of 1 × 10 19 W cm −2 and 7 µ m Cu foil target. Using the observed laser-to-x-ray conversion, the fast electron conversion efficiency was estimated to be ∼1%. Intensity scaling of x-ray conversion was used to establish the role of the J × B mechanism of fast electron generation. Furthermore, through parametric studies, the role of refluxing and reacceleration of electrons in x-ray generation is also established. Finally, the role of polarization ( p vs. s ) is also observed and briefly discussed.